Pemanfaatan Media Sosial sebagai Strategi Pemasaran Inovatif pada Start-Up Mahasiswa dan Calon Mahasiswa di Malaysia - Sih Darmi Astuti; Mahmud Mahmud; Naysila Angelli; Aliya Zahra; Julia Mulidawati; Maulidda Amanda Rossa; Alya Latiffa (Pusat Riset dan Inovasi Nasional, 2025)
Social media is now a very important factor especially for startups, especially in the early stages of growth and brand recognition. The Importance of Social Media as a Marketing Strategy for Startups Students and prospective students in Malaysia. With the increasing use of digital platforms, utilizing social media has become a crucial strategy to reach target audiences, build brand awareness, and increase customer interaction. Seeks to enhance students’ comprehension of the strategic role of social media in effectively marketing their goods and services. Without a social media presence, a startup is missing out on a huge opportunity to grow, be recognized, and connect with potential customers. It is not just about digital existence, but also about competitiveness and business continuity.